Pengaruh Kemiringan Lahan dan Mucuna bracteata terhadap Aliran permukaan dan Erosi di PT Perkebunan Nusantara V Kebun Lubuk Dalam - Suryanto Suryanto; Wawan Wawan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
One of the problems that became a threat to the sustainability of the ecosystem and the balance of the farm is land degradation caused by soil erosion due to rains. Elevation and topography that concerns with the land slope also gives effect to the surface run off rate and erosion. The use of Mucuna bracteata became one of efforts to address land degradation due to surface run off and soil erosion. This research uses Split Plot Design where the land slope as the main plots and the use of Mucuna bracteata swath as sub plots. The main plots consists of 3 levels namely land slope 0 - 8%, land slope 8 - 15% and land slope 15 - 25%, whereas the sub plots consists of 2 levels, namely the use of Mucuna bracteata and without the use of Mucuna bracteata. Research results show that the land slope and the use of Mucuna bracteata effects surface run off and erosion. Significantly the existence interaction between the land slope with the use of Mucuna bracteata. The positive correlation between the intensity of rain with surface run off, and surface run off with erosion. Keywords: land slope, the use of Mucuna bracteata, surface run off, erosion